Self Assessment System, Diskriminasi, dan Kemungkinan Terdeteksinya Kecurangan pada Persepsi Tax Evasion - Kumala Dewi, Ni Made Ratih; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
Tax evasion is a phenomenon that occurs in Indonesia. The perception of tax evasion views that the tax money paid is not used properly. The aim of this study is to empirically examine the effect of the self-assessment system, discrimination, and the possibility of detecting fraud on the perception of tax evasion. The research was conducted at KPP Pratama West Denpasar. Purposive sampling technique was used in this study and a sample of 100 individual taxpayers (WPOP) was found. Data analysis in this research used multiple linear regression analysis techniques. The results showed that the self-assessment system and the possibility of detecting fraud had a negative effect on perceptions of tax evasion, while discrimination had a positive effect on perceptions of tax evasion. The implication of this research is to provide support for the theory of planned behavior and attribution theory related to the factors that influence the perception of taxpayers in tax evasion. Keywords: Self Assessment System; Discrimination; Possibility Of Detecting Fraud; Perceptions In Tax Evasion